LIQUIDITY RATIO ANALYSIS OF PT. KIMIA FARMA (Persero) Tbk: 2019-2022 - Aditama Agustian; Parida Marjuliana; Hardiansyah; Nia Asdina; Rosidah; Widyawati (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2023)
This research aims to measure the financial performance of PT. Kimia Farma (Persero) Tbk, listed on the IDX, from 2019 to 2022 using liquidity ratios such as the Current Ratio (CR), Quick Ratio (QR), and Cash Ratio (CR). Employing quantitative methods, the study analyzed secondary data from the company's financial reports published by the IDX. The findings reveal that the company's financial condition is poor due to fluctuating and inconsistent performance each year. The highest current ratio was 105.8% in 2022, slightly above 105.4% in 2021, with the lowest at 89.7% in 2020, indicating a troubling decline. The quick ratio peaked at 66.3% in 2022 and hit a low of 53.5% in 2020, suggesting a reasonably good but inconsistent condition. The cash ratio reached a high of 26.8% in 2022 and a low of 12.5% in 2021, pointing to poor liquidity. Overall, the study shows that PT. Kimia Farma (Persero) Tbk does not exhibit strong or stable liquidity, as evidenced by the variations and declines in these ratios over the years.